Flexural Strength of Steel-Concrete Composite Beams Under Two-Point Loading - Sangeetha, Palanivelu; Ramana, Gopal S.; Jai, Vigneshwar A.; Vaishnavi, K.; Srinidhi, A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study investigates the flexural strength of simply-supported steel?concrete composite beams under two-point loading. A total of four specimens were tested to failure for varying parameters including type of connectors (stud and channel) and number of connectors (two and four). ANSYS software was used to establish the finite element models that can simulate the flexural behaviour of the composite beam.
Keywords: composite beam; steel-concrete beam; flexural strength; decking sheet; connector; load; belka zespolona; belka stalowo-betonowa; złącze; obciążenie; odkształcenia; ANSYS